If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13(4x + -7) = 13 Reorder the terms: 13(-7 + 4x) = 13 (-7 * 13 + 4x * 13) = 13 (-91 + 52x) = 13 Solving -91 + 52x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '91' to each side of the equation. -91 + 91 + 52x = 13 + 91 Combine like terms: -91 + 91 = 0 0 + 52x = 13 + 91 52x = 13 + 91 Combine like terms: 13 + 91 = 104 52x = 104 Divide each side by '52'. x = 2 Simplifying x = 2
| 8(3x+6)=96 | | 2(x+7)=56 | | s^2+s+4=0 | | 71-6x=35 | | 22+4x=50 | | y^2-4= | | 5x-73=27 | | 2Y^3-Y+3X-2=0 | | 6x+29=13x+41 | | s^2-s+4=0 | | (6x-7)+9x=68 | | 10x-117=5x-7 | | 8x^7y(5x^6y^2-6x^2+4y^3)= | | 5(2y+4)= | | -2+3(x-9)-2(x+3)=0 | | 2z^2+40=-8z | | 4+x=117 | | p+4p=60 | | 5x^2+30x-10=0 | | 3n+5=n-8 | | 3y(2y-4)=16 | | 3y(2y-4)=21 | | log*x^2-log*x=log*100 | | 3x-8+8=34 | | 4x+12=8x-36 | | -3x+x=-21 | | x^3+x^2-5x+3=0 | | 0,30*1044=x | | 7x+4y=18 | | 11=2x+3 | | x+5*13=559 | | 6x+7x=13x |